ORGANIZATION AND PROFESSIONALISM COMMITMENT AGAINST AUDITOR PERFORMANCE - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
This research is intended  to prove empirically: (1) The influence  of organizational commitment on the  auditor performance; (2) The influence of  professionalism on the auditor performance; (3) The influence of organizational commitment and professionalism  on the auditor performance.In this research, to get the accurate result, the writer uses associative approach. The population in this study are all auditors working in the public accounting firm in North Sumatra while sampling  is saturated sample. While  technique in collecting data, it is used  directly questionnaire to respondents, and  the method of data analysis is multiple linear regression.The result shows that: (1) organizational commitment significantly influences the performance of the auditor, (2) professionalism also influences  the auditor  performance, (3) organizational commitment and professionalism also give a great effect  on the auditor performance. Keywords: Organizational Commitment, Professionalism, Auditor Performance